Challenges and requirements for implementing due prominence: aligning stakeholder interests in Flanders - Van der Elst, Pieter; Afilipoaie, Adelaida; Raats, Tim (Frontiers in Communication, 2025)
Since the introduction of Article 7a in the Audiovisual Media Services Directive (AVMSD), which enables Member States to impose measures that ensure prominence of general interest services on user interfaces, discussions within media policy on the need of these measures have increased markedly. In Member States such as Germany, France, Italy and Ireland, commitments were already imposed on players offering user interfaces to audiovisual—and in some cases also audio—media services and content of general interest. This article presents the findings of a study examining the desirability and feasibility of implementing due prominence measures in Flanders (Belgium). The research adopts a media policy analytical approach and examines the (i) positions of the different stakeholders on the desirability and feasibility of a revised prominence regime, (ii) the extent to which interests across different stakeholders can be aligned and (iii) the considerations governments need to take into account when developing due prominence measures in Member States. The research is based on a stakeholder consultation conducted with broadcasters, television distributors, streaming services and hardware manufacturers operating in the Flemish market. The research is complemented with interviews with representatives of different market actors. The study identifies considerable oppositional logics between broadcasters and hardware manufacturers and raises challenges in defining the scope of ‘general interest’, the addressees of prominence measures, contextual factors such as markets size and path-dependency in media policy, and the commensurability between different existing legal frameworks at the national and EU level. The authors argue for clearer, more explicit guidelines at the EU level regarding the interpretation of Article 7a.